2016
DOI: 10.1038/srep35260
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Diamond Needle as Point Electron Source

Abstract: Diamond has been considered to be one of the most attractive materials for cold-cathode applications during past two decades. However, its real application is hampered by the necessity to provide appropriate amount and transport of electrons to emitter surface which is usually achieved by using nanometer size or highly defective crystallites having much lower physical characteristics than the ideal diamond. Here, for the first time the use of single crystal diamond emitter with high aspect ratio as a point ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The field electron emission in dark (without laser illumination) from similar diamond needles as the ones investigated in this work was reported in previous papers by Kleshch et al [19], Borz et al [20] and Terresin et al [24]. Two different behaviors in Fowler-Nordheim (FN) coordinates were reported: a linear behavior [18,20], as for the case of metallic field emitters, or a saturated behavior, as for the semi-conducting field emitters [19,24]. Even if non-doped bulk diamond is a wide-bandgap semiconductor, the metallic behavior was explained by transport of electrons via numerous defects and impurities at the surface of the diamond needle.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The field electron emission in dark (without laser illumination) from similar diamond needles as the ones investigated in this work was reported in previous papers by Kleshch et al [19], Borz et al [20] and Terresin et al [24]. Two different behaviors in Fowler-Nordheim (FN) coordinates were reported: a linear behavior [18,20], as for the case of metallic field emitters, or a saturated behavior, as for the semi-conducting field emitters [19,24]. Even if non-doped bulk diamond is a wide-bandgap semiconductor, the metallic behavior was explained by transport of electrons via numerous defects and impurities at the surface of the diamond needle.…”
Section: Resultssupporting
confidence: 79%
“…In particular, the diamond received a lot of attention due to its unique properties: chemical inertness, mechanical stability and high thermal conductivity [16,17]. In this sense, recent studies have demonstrated that diamond is an excellent candidate for field-emission cathode, in the dark or under ultrafast laser illumination [12,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“… for details) the FE current in the saturation region increased approximately by a factor of 2. Such kind of saturation as well as the sensitivity to light and temperature are usually observed for field emitters made of p‐type semiconductors . At low voltages, the FE current is determined by FN‐tunneling processes from the conduction band of the semiconductor into the vacuum.…”
Section: Resultsmentioning
confidence: 91%
“…Such kind of saturation as well as the sensitivity to light and temperature are usually observed for field emitters made of p-type semiconductors. [9,[17][18][19] At low voltages, the FE current is determined by FN-tunneling processes from the conduction band of the semiconductor into the vacuum. With increasing voltage, the FE current starts to be limited by the small concentration of carriers in the highly resistive depletion zone which is formed at the tip apex due to the strong penetration of the field into the emitter body.…”
Section: Resultsmentioning
confidence: 99%
“…First, semiconducting nanotubes have higher electrical resistance and during emission larger voltage drops can occur inside them which can cause pronounced saturation-like deviation from the classical FN behavior. [21] Moreover, the saturation behavior which is usually observed for semiconducting tip emitters [22,23] can be also explained by the formation of a highly resistive region (depletion zone) at the emitter apexes due to the penetration of the electric field. [24] The depletion zone limits the tunnelling current and results in nonlinear FN plots.…”
Section: Discussionmentioning
confidence: 99%